1998
DOI: 10.1002/(sici)1098-2256(1998)13:2<165::aid-tox8>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the toxicity of several dithiocarbamates using an Escherichia coli growth inhibition bioassay and the acetylcholinesterase inhibition test

Abstract: ABSTRACT:The industrial and sanitary use of dithiocarbamates DTCs is on the rise, and the synthesis of new derivatives has increased the field of their application. Both positive and negative pharmacological and toxicological effects have been documented for DTCs. The development and application of new DTCs must be accompanied by the study of their toxicity, beginning with the performance of simple and rapid biological screening tests.( ) The objective of our study was to apply the IGEC biotest inhibition of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…According to the literature, dithiocarbamates such as MCZ have minimal inhibitory effects on AChE activity (Espigares et al ). Although MCZ produces neurodegenerative effects as well, it is thought to primarily affect other neurotransmission subtypes such as the GABAergic or dopaminergic systems (Negga et al ; Brody et al ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, dithiocarbamates such as MCZ have minimal inhibitory effects on AChE activity (Espigares et al ). Although MCZ produces neurodegenerative effects as well, it is thought to primarily affect other neurotransmission subtypes such as the GABAergic or dopaminergic systems (Negga et al ; Brody et al ).…”
Section: Discussionmentioning
confidence: 99%
“…As colony-forming unit (CFU) assay in a particular test solution is a measure of the reproductive ability of E. coli, its metabolic inhibition or growth inhibition bioassay can be measured by counting the CFU. CFUbased assessment has proved to be a reliable measure of biotoxicity [10] and has been applied in our earlier studies [5,[11][12][13]. It is worth mentioning here that some authors have reported the disinfection of drinking water by AOPs including Fenton and Fenton-like processes by killing the micro-organisms [14,15].…”
Section: Introductionmentioning
confidence: 96%
“…As a colony forming unit (CFU) assay in a particular test solution is a measure of the reproductive ability of E. coli, its growth inhibition bioassay can be measured by counting the CFU. A CFU-based bioassay is a reliable measure of biotoxicity [10] and has been applied in several of our earlier studies. [4][5][6]11]…”
Section: Introductionmentioning
confidence: 99%